PRIVATIZATION IN SERBIA – AN ASSESMENT BEFORE THE LAST ROUND - Vujačić, Ivan; Petrović Vujačić, Jelica (Economic Annals, 2016)
Serbia has had a long history of privatization. It commenced in 1990 and was only fully completed, as defined by the privatization legislation, in 2015. The reasons for this are many and complex and the paper provides a short historical overview. Privatization, however, began in earnest after the democratic revolution of 2000 and the paper analyses the political motives behind the adoption of the current model. The paper goes on to explain the model design, as well as its dynamics and results. The analysis probes more deeply into the specific weaknesses of auction implementation, showing that an alternative approach could have produced better results in terms of revenue. The specific institutional flaws that led to a high failure rate in the privatization of companies are identified and analysed. These weaknesses lie in the design, implementation, and monitoring, which led to results that were not in line with the goals of the privatization process. The designers of the privatization model gave scant attention to broader institutional coherence, which enabled largescale manipulation of the process. In some cases this enabled motives unrelated to the future of the firm being privatized to dominate the process. Finally, the scope of the, last round of privatization in Serbia, which commenced in June 2015, and the probable results are discussed.